(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
The experiment was conducted at the Agriculture Field laboratory of Noakhali Science and Technology University, Noakhali, Bangladesh during the period from December 2020 to February 2021 to observe the effect of different levels of nitrogen (N) and phosphorus (P) fertilizer on growth and yield of lettuce. The experiment comprised of two factors. Two inorganic fertilizers like different level of nitrogen and phosphorus viz; nitrogen-control 0 kgha-1 (N0), 100 kgha-1 (Nı), 150 kgha-1 (N2) and 200 kgha-1 (N3) and phosphorus-control 0 kgha-1 (P0), 50 kgha-1 (P1), 62.5 kgha-1 (P2) and 75 kgha-1 (P3). The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Application of different levels of nitrogen and phosphorus significantly influenced the plant height, leaves number plant-1, leaf area, fresh leaf yield plant-1, gross yield, and dry matter content of lettuce. The maximum plant height, leaves number plant-1, leaf area, fresh leaf yield plant-1, gross yield and dry matter content were obtained with the application of 200 kg N ha-1. On the other hand, with the application of 75 kg P ha-1 the maximum plant height, leaves number plant-1, leaf area, fresh leaf yield plant-1, gross yield and dry matter content were found. In case of different treatment interaction, N3P3 (200 kg N ha-1 + 75 kg P ha-1) produced the highest gross yield (32.2 tha-1) and the lowest gross yield (16.11 tha-1) found from control treatment. Vol. 9, No. 2, August 2022: 125-134